A survey on ontology-based visualization techniques towards program comprehension application / Rozita Kadar, Jamal Othman and Naemah Abdul Wahab - Kadar, Rozita; Othman, Jamal; Abdul Wahab, Naemah (UiTM Cawangan Perlis, 2018)
A key challenge to software maintainers during performing the software maintenance is to comprehend a source code. Source code plays an important role in aiding software maintainers to get conversant with a software system since some system documentations are often unavailable or outdated. Although there are many researches that have discussed the different strategies and techniques to overcome the program comprehension problem, there exists only a shallow knowledge about the challenges software maintainers face when trying to understand a software system through reading source code. In order to make source code more comprehensible, it needs to make an enhancement regarding to the source code presentation by transforming it into a different view. From the literature review, we found that there are lacks of study that consider the use of knowledge representation to represent source code. Hence, the aim of this work is to review the existing techniques for source code representation based on knowledge representation that could help developers to reduce the amount of their effort needed to understand a source code.